Associations of leisure-time, occupational, and commuting physical activity with risk of depressive symptoms among Japanese workers: a cohort study - Kuwahara, Keisuke (Int J Behav Nutr Phys Act, 2015)
BACKGROUND: Leisure-time physical activity is associated with a lower risk of depression. However, the precise shape of the dose–response relationship remains elusive, and evidence is scarce regarding other domains of activity. We prospectively investigated associations of physical activity during leisure, work, and commuting with risk of depressive symptoms in Japanese workers. METHODS: We conducted a cohort study of 29 082 Japanese workers aged 20–64 years without psychiatric disease (including depressive symptoms) at baseline with a maximum 5-year follow-up. Physical activity was self-reported. Depressive symptoms were assessed by 13 self-report questions on subjective symptoms. Hazard ratios (HRs) and 95 % confidence intervals (CIs) for incidence of depressive symptoms were calculated using Cox regression analysis. RESULTS: During a mean follow-up of 4.7 years, 6177 developed depressive symptoms. Leisure exercise showed a U-shaped association with risk of depressive symptoms adjusting for potential confounders. Additional adjustment for baseline depression scores attenuated the association, but it remained statistically significant (P for trend = 0.037). Compared with individuals who engaged in sedentary work, the HR (95 % CI) was 0.86 (0.81, 0.92) for individuals who stand or walk during work and 0.90 (0.82, 0.99) for those who are fairly active at work. However, the association disappeared after adjusting for baseline depression scores. Walking to and from work was not associated with depressive symptoms. CONCLUSIONS: The findings suggest that leisure-time exercise has a U-shaped relation with depressive symptoms in Japanese workers. Health-enhancing physical activity intervention may be needed for individuals who engage in sedentary work.